Pembelajaran Anak Berkebutuhan Khusus di PAUD Alam Bengkulu Mahira Kota Bengkulu - Yartika Yartika; Agus Zainal Ramat; M Izzudin (UNIB Press, Universitas Bengkulu, 2019)
This study aimed to find out the learning strategy of exceptional children in the Mahira Natural Kindergarten Bengkulu City. The method used is qualitative method with descriptive approach. Based on the result of the research and discussion, it is concluded that (1) the expectation / target in the learning of exceptional children are 7 development targets that are the the development of religious and moral values target, physical development target, cognitive development target, language development target, emotional social development target, self-building development target, and science development target. (2) Determination of the learning time allocation of exceptional children is within 1 week, it taken 1 hour to follow the learning activities in inclusion. For the rest, the exceptional children still followed the regular children learning. (3) Preparation of rewards/gift for exceptional children, there are three forms. First is physical form, such as food, snacks and toys. Second form is a gift / rewards given by the teacher in a verbal form, where gifts / rewards are given such as praise and motivation. Then the third gift / rewards in non verbal form such as hugs, thumbs up, applause, and tos together. (4) Provision of tasks / work for exceptional children. There are two forms of tasks. First is general task where general task form given same with the regular children, but the general task given still depends on the ability of the children itself. Second is a special task, where the task is designed specifically for exceptional children in accordance with the target of each children. (5) Provision of special assistance for exceptional children, there are three forms. First is physical assistance, where the assistance is provided directly to the exceptional children with direct physical touch. Then the second is verbal assistance, the help given such as teach the children to say hello, greet friends and say thank you. Then the third is emotional assistance, where the assistance is provided by helping to reduce emotions. (6) In the learning process, the themes and subjects given for the children are same, both for regular class and exceptional children. But different in the burden of learning given. Keywords: Learning, Exceptionl Children, Mahira Natural Kindergarten Bengkulu